Beyond Resilience and Trauma: Seven Post-Crisis Identity Trajectories Through the Transcultural Positive Psychotherapy Lens - Gordienko-Mitrofanova, Iya; Sukhan, Viktoriia (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2026)
Aim. The article presents the results of the empirical verification and theoretical expansion of the "Integrative Model of Existential Choice and Adaptation" (Iteration 1.2). The study aims to specify post-crisis identity trajectories among the civilian population during prolonged warfare, while substantiating the mediating role of resource spheres and the moderating role of existential continuums within the adaptation process. Methods. A sequential mixed-methods design was employed (N > 600). The empirical corpus comprised 102 semi-structured narrative interviews with residents of Kharkiv and the surrounding region, analyzed using reflexive thematic analysis (codebook approach). Additionally, an original five-step self-reflection tool was piloted (N > 400) using descriptive statistics to evaluate the subjective effectiveness of guided self-help interventions. Results. The findings support expanding the typology of belonging identity from three to seven distinct trajectories: transformed local, alienated local, multi-local, temporary evacuation, mono-local, liminal, and reintegrated. The "Activity" sphere (R2) was identified as an autonomous resource module facilitating the regulatory mechanism of adaptation. The functional roles of variables were formalized: existential continuums (C1–C6) act as moderators, while resource spheres (R1–R4) serve as mediators in the integration of traumatic experience. The dynamic coexistence of post-traumatic growth (PTG) and post-traumatic depreciation (PTD) was conceptualized as the predominant adaptive pattern. Conclusions. Successful adaptation is determined by the capacity for cognitive structuring of experience and the existential choice alignment with the selected identity trajectory. The developed self-reflection tool is validated as an effective psychological instrument, bridging the transcultural positive psychotherapy principles with evidence-based practice.